ASPEC: Adaptive Spectral Perceptual Entropy Coding of High Quality Music Signals - Brandenburg, Karlheinz; Herre, Jürgen; Johnston, J D; Mahieux, Y; Schroeder, E F (90th AES Convention, 1991)
ASPEC is the joint proposal of AT&T Bell Laboratories, Thomson Consumer Electronics, Fraunhofer Society and CNET for the audio coding standard which is drafted by the ISO/IEC JTC1/SC2/WG11 audio experts group (MPEG-Audio). It combines high coding efficiency with the flexibility needed to work in different applications, from 64 kbps per channel with FM quality to 128 kbps for CD quality. The algorithm is suitable for uses such as ISDN audio transmission, fixed and writable storage applications, and Digital Audio Broadcasting.
herre_papers_perceptual_audio_coding